Zoonoses Surveillance in Italy (2000-2009): Investigation on Animals with Neurological Symptoms - Casalone, Cristina; Iulini, Barbara; Pintore, Maria Domenica; Maurella, Cristiana; Bozzetta, Elena; Cantile, Carlo; Gandini, Gualtiero; Capucchio, Maria Teresa; Calistri, Arianna; D'angelo, Antonio; Caramelli, Maria (IntechOpen, 2011)
None